2017
DOI: 10.1111/jicd.12307
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between the maxillary sinus floor and the upper posterior root tips: Clinical considerations

Abstract: Understanding the relationship between the maxillary sinus floor and the upper posterior root tips is important to the clinician when performing conventional or surgical endodontic treatment and conventional surgery procedures in order to minimize or avoid the risk of damaging the maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
14
1
3
Order By: Relevance
“…First molars in contact with MS (Table 2) were in the present study considerably more prevalent than in an earlier study that measured the number of 1st molars protruding into the MS (Nino- Barrera et al, 2018). Although, it is important to notice that the way of grouping the measurements differ from current studies.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…First molars in contact with MS (Table 2) were in the present study considerably more prevalent than in an earlier study that measured the number of 1st molars protruding into the MS (Nino- Barrera et al, 2018). Although, it is important to notice that the way of grouping the measurements differ from current studies.…”
Section: Discussioncontrasting
confidence: 83%
“…The present study includes protruding roots and roots that touch the MS in one group, while other studies separate them. The result of previous studies assessing molars roots in contact with MS; 20-63% for second upper molars, 25-84% for first upper molars (Kilic et al, 2010;Nino-Barrera et al, 2018;Shahbazian et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…18,[23][24][25][26][27][28] Other studies reported that the palatal root of the first molar most frequently protruded into the sinus. 19,[29][30][31][32] Our results revealed that the type 3 (root protrusion into the sinus) configuration occurred most frequently in the mesiobuccal root of maxillary second molars (48.4%), while type 2 occurred most frequently in the palatal root of maxillary first molars (43.1%). Previous studies have reported that the palatal roots of second molars exhibited the lowest incidence of protrusion into the sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Panoramic radiography is the main imaging technique used to evaluate the close relationship between the maxillary posterior roots and maxillary sinus; however, the assessment of the relationship between the upper teeth roots and maxillary sinus has shown that panoramic radiography and CBCT are significantly different techniques. 18,19 Despite image-distortion problems and lack of acutance, panoramic radiography has been reported to be useful in most routine clinical situations and an important tool in determining the need for preoperative CBCT scanning. 20,21…”
Section: Discussionmentioning
confidence: 99%